BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Rony Jaya (Universitas Riau, 2016)
Organizational Culture, Organizational Commitment and Organizational Citizenship Behavior (OCB). This study aims to finding out and analyzing the influence of organizational culture and organizational commitment to Organizational Citizenship Behavior (OCB) employees at the Integrated Service Agency and Investment (BPTPM) Pekanbaru. The study population was all employees numbering 85 people, researchers take 46 people with the withdrawal of random sampling techniques. Methods of data collection by distributing questionnaires filled out by respondents employees besides, the researcher also reviewed the literature. Methods of data analysis using multiple linear regression using SPSS version 20. The aid application results showed that the partial organizational culture does not significantly influence the OCB. While the organizational commitment and significant positive effect on OCB employee BPTPM Pekanbaru. Simultaneously, organizational culture and organizational commitment and significant positive effect on Organizational Citizenship Behavior (OCB). The coefficient of determination of organizational culture and organizational commitment on OCB is as much as 65.4%. While the rest is as much as 34.6% is indicative of other factors not examined in this study.